2015
DOI: 10.1061/(asce)wr.1943-5452.0000459
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Assessment of Water, Food, and Energy Trade-Offs in a Cascade of Multipurpose Reservoirs: Case Study of the Sesan Tributary of the Mekong River

Abstract: The Mekong River Basin in Southeast Asia is undergoing rapid development in the exploitation of its water resources. Although hydropower is the most dominant driver for water development, the possibilities for multipurpose reservoirs have been increasingly discussed but not well studied. The authors assess the potential benefits and negative impacts of a multipurpose reservoir cascade facilitating hydropower and irrigation in the Sesan River, a transboundary tributary of the Mekong. A model-based assessment ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Their complementary (or conflicting) effects with hydropower, however, are important for water resources management and should be the subject of further research. Thus far, water withdrawals for agricultural production have not been found to be conflicting significantly with hydropower in this basin (Räsänen et al ., ). Preliminary modelling on climate change and hydropower operations suggests that hydropower operations have the greatest impact on seasonal flow patterns and that energy production will not be substantially affected by impacts of climate change on basin hydrology (Piman et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Their complementary (or conflicting) effects with hydropower, however, are important for water resources management and should be the subject of further research. Thus far, water withdrawals for agricultural production have not been found to be conflicting significantly with hydropower in this basin (Räsänen et al ., ). Preliminary modelling on climate change and hydropower operations suggests that hydropower operations have the greatest impact on seasonal flow patterns and that energy production will not be substantially affected by impacts of climate change on basin hydrology (Piman et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Future irrigation water demands, land use change and climate change have been studied in this basin before (Ty et al ., ; Piman et al ., ; Räsänen et al ., ); thus, these factors were not considered in this study. Their complementary (or conflicting) effects with hydropower, however, are important for water resources management and should be the subject of further research.…”
Section: Discussionmentioning
confidence: 99%
“…The authors proposed that downstream countries could provide alternative energy sources to Kyrgyzstan in exchange for releasing irrigation water during the irrigation season, essentially reverting to the Soviet era flow release regime. On the other hand, Räsänen et al (2015) found that multipurpose cascade reservoirs on a transboundary tributary of the Mekong created considerable irrigation potential at the expense of a relatively small hydroelectricity generation loss. Another study in the Nam Ngum, a sub-basin of the Mekong, similarly showed that full hydropower development allowed irrigation water use to triple and also improved environmental flow requirements during low-flow periods (Lacombe et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…When discussing the nexus, it is useful to recognise that it has different dimensions: we discuss what we consider to be the two key dimensions of the nexus. The first dimension promotes the nexus as an approach for research and analysis by, for example, quantifying the linkages between the nexus sectors [1,6,[21][22][23]. The second dimension presents the nexus more as a policy-making tool that is seen to facilitate cross-sectoral collaboration and integrated planning and policy-making [3, 4,9,24].…”
Section: Introductionmentioning
confidence: 99%